Cold stress induces rapid gene-specific changes in the levels of H3K4me3 and H3K27me3 in Arabidopsis thaliana - Faivre, Léa; Kinscher, Nathalie-Francesca; Kuhlmann, Ana Belén; Xu, Xiaocai; Kaufmann, Kerstin; Schubert, Daniel (Frontiers in Plant Science, 2024)
When exposed to low temperatures, plants undergo a drastic reprogramming of their transcriptome in order to adapt to their new environmental conditions, which primes them for potential freezing temperatures. While the involvement of transcription factors in this process, termed cold acclimation, has been deeply investigated, the potential contribution of chromatin regulation remains largely unclear. A large proportion of cold-inducible genes carries the repressive mark histone 3 lysine 27 trimethylation (H3K27me3), which has been hypothesized as maintaining them in a silenced state in the absence of stress, but which would need to be removed or counteracted upon stress perception. However, the fate of H3K27me3 during cold exposure has not been studied genome-wide. In this study, we offer an epigenome profiling of H3K27me3 and its antagonistic active mark H3K4me3 during short-term cold exposure. Both chromatin marks undergo rapid redistribution upon cold exposure, however, the gene sets undergoing H3K4me3 or H3K27me3 differential methylation are distinct, refuting the simplistic idea that gene activation relies on a switch from an H3K27me3 repressed chromatin to an active form enriched in H3K4me3. Coupling the ChIP-seq experiments with transcriptome profiling reveals that differential histone methylation only weakly correlates with changes in expression. Interestingly, only a subset of cold-regulated genes lose H3K27me3 during their induction, indicating that H3K27me3 is not an obstacle to transcriptional activation. In the H3K27me3 methyltransferase curly leaf (clf) mutant, many cold regulated genes display reduced H3K27me3 levels but their transcriptional activity is not altered prior or during a cold exposure, suggesting that H3K27me3 may serve a more intricate role in the cold response than simply repressing the cold-inducible genes in naïve conditions.